PENINGKATAN HASIL BELAJAR IPA MENGGUNAKAN PENDEKATAN INKUIRI DI SD - YULISNI, ZULMA (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This Inkuiri based on the reality in the elementary school whis is learn dominated by teacher and used conventional method commonly as learning model. The purpose of this inkuiri to describe the increasing IPA subject by using model of inkuiri type around planing, doing and learning result. The approach that used is kualitative and kuantitative with containts of 4 steps that are planing, doing, monitoring and practicing. The inkuiri subject is fourth grade students of elementary school at  SDN 04 Sasak Ranah Pasisie Kab. Pasaman Barat. From analysis data can be resulted that method inkuirit can increase students marks in studying.   Kata kunci : hasil belajar ; pembelajaran IPA ; pendekatan inkuiri